On the asymptotics of the mean sojourn time of a random walk on a semi-axis. (June 2015) - Lotov, V. I.; Tarasenko, A. S.
Abstract: We find asymptotic expansions for the expectation of the sojourn time above an increasing level of a trajectory of a random walk with zero drift. The Cramér condition on the existence of an exponential moment is imposed on the distribution of jumps of the random walk.